(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The focus of this study is on the symbolic functions of words in a given context that upholds expert opinion as a background or theoretical framework. According to the theory, language is made up words that are put together in a context to improve communication among people who share the same linguistic boundaries. In light of the foregoing, the study focuses primarily on the roles words play in communication in a given situation. Technical terms like agent, theme and instrument are used for analytical purposes. The study affirms that while every word has a meaning, its social application affects how we communicate on a day-to-day basis.